Horta sensorial como apoio aos professores de ciências naturais no contexto da educação inclusiva - Santos, Eurico Cabreira dos (2015)
In recent decades, inclusive education has gained evidence through social movements with various achievements of legal guarantees waving with the possibility for an improvement in their social status, study and accessibility. However, laws alone are no guarantee that their rights are respected, if these rights are not worked for Education. This research aimed to study the greenery species for use in sensory garden to support the continuing education of teachers who work with students 'normal' and visually impaired. This study was carried out from March to November/2014 in municipality of Cáceres, Mato Grosso State; in a state school Dr. José Rodrigues Fontes a state school education working in the perspective of inclusive education. To make the experiment with plants was implemented a garden suspended for the cultivation of vegetables and later held the sensory evaluation to know the effective status. In this evaluation employees (blind) made a careful analysis of all morphological structures and plant architecture, then based on the scores of hedonic scale attributed the concepts. The results were favorable because of the 17 plants evaluated, 14 had the maximum concepts enjoyed and liked the concept 03, based on these concepts can be concluded that all plants have awakened the feeling of pleasure in people. Also as a result, a pedagogical guide was built as teaching material with suggestions of educational activities for teaching science using the techniques of scientific illustration for seers students and for blind students was built planks in relief of morphological structures of plants and evaluated by students visually impaired. We believe that the results were favorable with respect to the evaluated plants and will inform teachers in science education aimed at working the concepts of botany, especially the work related to morphological structures of plants for the students of inclusive education.